Strategy for implementing segmentation, targeting, and positioning to increase the utilization of outpatient services in hospitals - Sukarjiyah, Waritsah; Wiliyanarti, Pipit Festi; Sukardiono, Sukadiono (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Bckground: Hospitals have a responsibility to provide quality, affordable, and accessible healthcare services to all levels of society. Varied patient needs and characteristics often pose challenges in optimizing visits and maintaining service quality, particularly in outpatient care. Implementing a segmentation, targeting, and positioning (STP) strategy can be an effective service management approach to tailoring services to patient profiles, thereby supporting increased service utilization and enhancing patient satisfaction. Purpose: To systematically review the application of STP strategies in hospital settings and to identify their role in enhancing the utilization of outpatient services, with a focus on patient-centered care and health service accessibility. Method: A systematic review was conducted following PRISMA 2020 guidelines. Literature was searched through the Scopus database. A total of 20 articles that met the inclusion criteria were analyzed. Results: Hospitals apply segmentation strategies (demographic, psychographic, behavioral), targeting (specific patient groups, medical tourism, service-based targeting), and positioning (faith-based service values, patient-centered care, experience-based branding). These approaches have been shown to increase patient satisfaction, loyalty, and particularly the utilization of outpatient services. Conclusions: This review demonstrates that segmentation, targeting, and positioning (STP) strategies, although traditionally applied in hospital service strategies can be effectively adapted to optimize outpatient healthcare services. The novelty of this study lies in reframing STP as a health service management approach that enhances patient-centered care, increases service utilization, and supports broader public health outcomes.